Karakteristik Makroskopis Dan Mikroskopis Jamur Kontaminan Pascapanen Pada Buah Jeruk Madu Berastagi di Desa Seribu Jandi Sumatera Utara - Tarigan, Emilia Surabina Br; Sartini, Sartini; Rahmiati, Rahmiati; Lubis, Rosliana (Universitas Medan Area, 2025)
This study aims to determine the types of fungi that contaminate post-harvest Berastagi honey orange fruit. The type of research is descriptive qualitative. The method used is the blocksquare method. The stages in the study include preparation of test media, isolation of contaminant fungi in honey orange fruit, pure culture techniques, measurement of fungal diameter in growth media, macroscopic and microscopic identification of fungi. The results of the study found three (3) genera with 14 isolates of post-harvest contaminant fungi. The first genus Fusarium with one species Fusarium sp. The second genus Penicillium with one species, namely Penicillium sp, the third genus Aspergillus with 12 species, namely Aspergillus sp1, Aspergillus sp2, Aspergillus sp3, Aspergillus sp5 Aspergillus sp5, Aspergillus sp6, Aspergillus sp7, Aspergillus sp8, Aspergillus sp9, Aspergillus sp10, Aspergillus sp11, and Aspergillus sp12. Two (2) unidentified isolates, namely Mycelia sterilia sp1 and Mycelia sterilia sp2. The isolates found had varying characteristics of texture, colony color and spore color. The conclusion obtained from this study was that the 16 fungal isolates consisted of three genera Fusarium, Aspergillus, Penicillium and two unidentified isolates, namely Mycelia sterilia.